2021
DOI: 10.3892/etm.2021.10250
|View full text |Cite
|
Sign up to set email alerts
|

Zwint facilitates melanoma progression by promoting c‑Myc expression

Abstract: ZW10 interactor (Zwint) is upregulated in various types of tumors and exerts a carcinogenic effect. However, little is known about the expression profile, function and molecular mechanisms of action of Zwint in melanoma. Therefore, the aim of the present study was to investigate the expression levels of Zwint in melanoma cell lines and tissues. It was revealed that Zwint was highly expressed in melanoma samples. Functional experiments indicated that Zwint knockdown suppressed the proliferation and migration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
(45 reference statements)
1
4
0
Order By: Relevance
“…Mechanistically, ZWINT knockdown decreases the protein expression levels of c-MYC, MTOR, phosphorylated MTOR, pp38, and fibronectin, while c-MYC overexpression reversed the effects on melanoma cell proliferation and migration. ZWINT was found to be downregulated in response to HSN748 treatment compared with DMSO, as was the expression of MYC; consistent with Mou et al’s ( 36 ) studies. Importantly, genes that contribute to Gilteritinib resistance, including AURKA and AURKB were found to be downregulated in HSN748-treated cells compared with DMSO ( Figure 5B ).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Mechanistically, ZWINT knockdown decreases the protein expression levels of c-MYC, MTOR, phosphorylated MTOR, pp38, and fibronectin, while c-MYC overexpression reversed the effects on melanoma cell proliferation and migration. ZWINT was found to be downregulated in response to HSN748 treatment compared with DMSO, as was the expression of MYC; consistent with Mou et al’s ( 36 ) studies. Importantly, genes that contribute to Gilteritinib resistance, including AURKA and AURKB were found to be downregulated in HSN748-treated cells compared with DMSO ( Figure 5B ).…”
Section: Resultssupporting
confidence: 87%
“…The analysis in Edward et al ( 35 ) of the TCGA pan-cancer data set revealed a greater frequency of the ZWINT mutation in Fanconi anemia mutant-associated cancers than in Fanconi anemia WT cancers. Recent studies by Mou et al ( 36 ) showed ZWINT knockdown inhibits the proliferation and migration of A375 melanoma cells. Mechanistically, ZWINT knockdown decreases the protein expression levels of c-MYC, MTOR, phosphorylated MTOR, pp38, and fibronectin, while c-MYC overexpression reversed the effects on melanoma cell proliferation and migration.…”
Section: Resultsmentioning
confidence: 99%
“…ZWILCH is an essential component of the mitotic spindle assembly checkpoint necessary for pausing metaphase transition to anaphase until chromosomes are properly attached to the kinetochore. 66 Overexpression of ZWILCH and other related mitotic checkpoint proteins has been previously associated with cancer progression, 67 - 69 and there is a strong negative correlation between ZWILCH mRNA levels and patient survival in the SU2C dataset 6 ( Figure S4E ). As such, we sought to determine how this 3′ UTR mutation affects cell growth.…”
Section: Resultsmentioning
confidence: 78%
“…Previous researches reported miR-204, a microRNA as a tumor suppressor gene, inhibited the proliferation of breast cancer by binding to the 3'-UTR site of ZWINT(G. Zhou et al, 2020). ZWINT promotes the proliferation and migration of melanoma by regulating the expression of c-Myc (Mou et al, 2021). miR-1 binds to its target gene ZWINT to promote prostate cancer progression (Xie et al, 2018).…”
Section: Discussionmentioning
confidence: 99%